2019
DOI: 10.4000/discours.9997
|View full text |Cite
|
Sign up to set email alerts
|

Domains and Functions: A Two-Dimensional Account of Discourse Markers

Abstract: Discourse markers and their functions have been modeled through a large number of very diverse frameworks. Most of these models target written language and the discourse relations that hold between sentences. In this paper, we present, assess and apply a new annotation taxonomy that targets discourse markers (instead of discourse relations) in spoken language and addresses their polyfunctionality in an alternative way. In particular, its main innovative feature is to distinguish between two independent layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(96 citation statements)
references
References 19 publications
8
78
4
Order By: Relevance
“…We have observed that the ni que insubordinates are normally triggered by the previous linguistic or extra-linguistic context, which is not surprising, considering that, as the data examined show, the ni que sequence acts as a discourse marker within the expressive/emotive domain, and as such any contextual cue in its interpretation is crucial (cf. Crible and Degand 2019). Consider this fact in (10), where both the linguistic and extralinguistic contexts make for the whole meaning of ni que as an interpersonal emotive marker.…”
Section: Discussion and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We have observed that the ni que insubordinates are normally triggered by the previous linguistic or extra-linguistic context, which is not surprising, considering that, as the data examined show, the ni que sequence acts as a discourse marker within the expressive/emotive domain, and as such any contextual cue in its interpretation is crucial (cf. Crible and Degand 2019). Consider this fact in (10), where both the linguistic and extralinguistic contexts make for the whole meaning of ni que as an interpersonal emotive marker.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…As can be seen, we herein adopt the term domain, taken from Crible and Degand (2019) to refer to "macro-functions which roughly correspond to the speaker's intention and degree of involvement" (2019: 4). Domains are thus understood as clusters of functions which, as a general category, can integrate more specific discourse functions but which are considered independent from the latter (Crible and Degand 2019: 4).…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In scientific literature, such devices are referred to as discourse markers. Though their main function is to convey coherence of a message, they are also used to express the attitudes towards the message and its addressee (Crible & Degand, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The latter was operationalized throughCrible and Degand's (2019) framework, where four discourse domains are distinguished: rhetorical uses, where discourse markers connect ideas, opinions or express the speaker's subjectivity (Example 9);• sequential uses, where discourse markers signal major transitions (topics or turns) and regulate the flow of speech (Example 10); grave oui euh mais pas dans la même manière the topic was uh when someone cheats on their boyfriend or something it's serious yes uh mais 'but' not in the same way (10) parce que c'est mal de laisser da:ans croire qu'il a raison alors que pas du tout donc euh imaginons on est dans le cadre d'une dispute…”
mentioning
confidence: 99%